Relations between attitudes and social representations: A conceptual integration (2007)
The attitudes and social representations are competing, alternative research programs to explain psychosocial phenomena. The study of the attitudes has followed a mentalist tradition while some argue that social representations are embedded in a sociological perspective. Since both attitudes and social representations stand on different research paradigms, some authors consider that they are incompatible to each other. We argue that the conceptual integration of both concepts is feasible if they are conceived within a genetic-structural perspective of social representations. From the structural perspective attitudes can be assumed as primary components of social representations. But, the structural perspective supposes a challenge for the theory of social representations if subsumed under a mentalist tradition of social psychology.